Mobbing - et forsøk på nye teoretiske perspektiv - Nome, Dag (Studier i Pædagogisk Filosofi, 2014)
This article discusses the understanding of bullying and how it ﬁrst appears as a phenomenon in early childhood. Empirical research on the social life of young children indicates a capacity for empathy that is independent of social learning. Based upon Merleau-Ponty`s philosophy of the body and Levinas’s existentialist notion of the origin of morality, the article emphasize empathy and the sense of responsibility as a fundamental event in our initial encounter with one another – not learned competence based on cognitive reﬂ ections. Anti-social behavior like bullying is therefore considered to be a narrowing of the initial openness for others entering our life-world, not a result of a natural urge to power and dominance.